The history of Taiwan - Li, Xiaobing 1954- (Greenwood, 2019)
"This one-volume handbook explores the history of Taiwan, from its prehistory to its Japanese colonization to its tumultuous relationship with China in the 21st century"--
Keywords: Geschichte; Taiwan; Taiwan / History; History